Critiquing free speech : First Amendment theory and the challenge of interdisciplinarity - Bunker, Matthew D. (LEA's communication series., 2001)
In this exceptional volume, Matthew D. Bunker explores the work of contemporary free speech critics and argues that, while at times these critics provide important lessons, many of their conclusions must be rejected. Moreover, Bunker suggests that we be w.